Poly (rC) binding protein 2 interacts with VP0 and increases the replication of the foot-and-mouth disease virus - Li, Dan (Cell Death Dis, 2019)
Foot-and-mouth disease virus (FMDV) causes a highly contagious and debilitating disease in cloven-hoofed animals, which leads to devastating economic consequences. Previous studies have reported that some FMDV proteins can interact with host proteins to affect FMDV replication. However, the influence of the interactions between FMDV VP0 protein and its partners on FMDV replication remains unknown. In this study, we found that the overexpression of poly (rC) binding protein 2 (PCBP2) promoted FMDV replication, whereas the knockdown of PCBP2 suppressed FMDV replication. Furthermore, PCBP2 can interact with FMDV VP0 protein to promote the degradation of VISA via the apoptotic pathway. Further studies demonstrated that FMDV VP0 protein enhanced the formation of the PCBP2-VISA complex. Ultimately, we found that the degradation of VISA was weaker in PCBP2-knockdown and FMDV VP0-overexpressing cells, or FMDV VP0-knockdown cells than in the control cells. Summarily, our data revealed that the interaction between PCBP2 and VP0 could promote FMDV replication via the apoptotic pathway.